Content of Polycyclic Aromatic Hydrocarbons in the Road Asphalt in Olecko - Chrząścik, Ireneusz; Szymalska, Magdalena; Kluska, Mariusz (Studia Ecologiae et Bioethicae, 2008)
Estimation of Polycyclic Aromatic Hydrocarbons (PAHs) in the road asphalt produced in different years in Poland was presented. Attention was paid especially to risks resulting from contact with asphalt and negative influence on life and health of road users. All 5 hydrocarbons recognized by WHO as compounds with carcinogenic activity and have been found in investigated samples, the results are situated between 0.1 and 60 pg/kg of dry mass. Simultaneously, it is necessary to emphasize, that asphalt consist of 90 % of aggregates and 10% ofbinder which contains these analyzed compounds.